Study of the effective fraction of areca nut husk fibre composites based on mechanical properties - Akbar, Irfan Muhammad; Fauza, Anna Niska; Abadi, Zainal; Rahmadiawan, Dieter (Researcher and Lecturer Society, 2024)
Areca nut husk fibers have the potential to be used as reinforcement in polymer composites as a substitute for synthetic fibres. In the manufacture of fibre composites, one of the important factors in determining the strength is the matrix to fibre ratio. This study aims to determine the effective ratio or fraction between areca nut husk fibre and orthophthalic polyester resin. Before using areca nut husk fibre, it was chemically treated so that only cellulose remained in the fibre. The areca nut husk fibre was processed into sheets. The composite was manufactured using the hand lay-up technique. Tensile and flexural tests were carried out to determine the mechanical properties. Based on the results of the tests conducted, there are differences in the mechanical properties of the composites. The tensile test results show that the 40% fibre fraction has the highest tensile strength and modulus values. On the other hand, in the flexure tests, the highest tensile strength and modulus values are found in the 30% fibre fraction.